Beijing and Haarlem Genotypes Are Overrepresented among Children with Drug-Resistant Tuberculosis in the Western Cape Province of South Africa - Marais, Ben J. (American Society for Microbiology, 2006)
Drug resistance among children with culture-confirmed tuberculosis (TB) provides an accurate measure of transmitted drug resistance within the community. We describe the genotype diversity in children with culture-confirmed TB and investigate the relationship between genotype and drug resistance. A prospective study was conducted from March 2003 through August 2005 at Tygerberg Children's Hospital, in the Western Cape Province of South Africa. All children (<13 years of age) diagnosed with culture-confirmed TB were included. Genotype analysis and phenotypic drug susceptibility testing were performed on the first culture-positive isolate from each patient. Mutation analysis was performed on all drug-resistant isolates. Spoligotyping was successfully performed on isolates from 391/399 (98%) children diagnosed with culture-confirmed TB. Drug susceptibility testing was also performed on 391 isolates; 49 (12.5%) were resistant to isoniazid, and 20 (5.1%) of these were resistant to both isoniazid and rifampin. Beijing was the most common genotype family, identified in 130/391 (33.2%) cases, followed by LAM in 114/391 (29.2%) cases. The presence of both Beijing and Haarlem genotype families was significantly associated with drug resistance (26/49 [53.1%] versus 113/342 [33.0%]; odds ratio, 1.7; 95% confidence interval, 1.0 to 2.9). The high prevalence of Beijing and LAM in children with culture-confirmed TB reflects considerable transmission of these genotype families within the community. The overrepresentation of Beijing and Haarlem genotype families in children with drug-resistant TB demonstrates their contribution to transmitted drug resistance and their potential importance in the emergent drug-resistant TB epidemic.